Active Interview Tactics Revisited: A Multigenerational Perspective - Hathaway, Andrew D.; Sommers, Rory; Mostaghim, Amir (Qualitative Sociology Review, 2020)
William (Billy) Shaffir taught about what it means to be a true empiricist, a sociologist committed to naturalistic observation as the most incisive method in our scientific toolbox. His inspiration still resonates, two decades later, in the work of new emerging scholars with the same commitment to ethnography—or what Billy more modestly and wisely calls “hanging around.” This paper is a tribute to his legacy that highlights the contributions of the next generation of graduate students that the lead author has been privileged to mentor at the University of Guelph. It builds on work by Hathaway and Atkinson on tactics of active interviewing to establish a more nuanced understanding of the benefits and challenges of being recognized as either an “insider” or “outsider,” and the implications of attempting to be both.